2013
DOI: 10.1063/1.4811010
|View full text |Cite
|
Sign up to set email alerts
|

Solar energetic particle characteristics and their dependence on longitude in solar cycle 24

Abstract: Abstract. In previous solar cycles, most studies examining the longitude dependence of solar energetic particle (SEP) event characteristics (such as composition and spectral hardness) have involved statistical analysis of single-point measurements. With the significant separation between the two STEREO and near-Earth spacecraft during solar cycle 24, these SEP characteristics can be examined simultaneously from multiple vantage points. Using SEP measurements from sensors on STEREO and ACE, we have examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Their modeling results showed a complicated picture of the Fe/O composition ratio, with dependence on the shock angle, the seed particle population, and heliocentric distance. Recent observations summarized in [10,19] and modeling results (see for instance [20]) indicate that one cannot easily distinguish between impulsive and gradual events using the Fe/O ratio at energies above ∼10 MeV/nuc, and the ratio of SEP Fe/O 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 can trend up or down depending upon heliocentric radial distance. On the other hand, there is observational evidence of the blurring of the distinction between gradual and impulsive events [7,6].…”
Section: Observational Evidence Of the Blurring Of The Distinction Bementioning
confidence: 98%
See 1 more Smart Citation
“…Their modeling results showed a complicated picture of the Fe/O composition ratio, with dependence on the shock angle, the seed particle population, and heliocentric distance. Recent observations summarized in [10,19] and modeling results (see for instance [20]) indicate that one cannot easily distinguish between impulsive and gradual events using the Fe/O ratio at energies above ∼10 MeV/nuc, and the ratio of SEP Fe/O 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 can trend up or down depending upon heliocentric radial distance. On the other hand, there is observational evidence of the blurring of the distinction between gradual and impulsive events [7,6].…”
Section: Observational Evidence Of the Blurring Of The Distinction Bementioning
confidence: 98%
“…(2013) [19] showed that neither geometry-controlled effects nor presence of flare-accelerated particles in the seed population can alone explain elemental 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 abundance (Fe/O) ratio in observed SEP events.…”
Section: Composition Of the Pre-accelerated Particlesmentioning
confidence: 99%
“…The physical characteristics of a particular SEP event are determined by a number of factors, e.g., seed population, preconditioning of the heliospheric environment (concomitant or preceding flares, preceding CMEs), and obliquity of the shock front connected to an observer [ Tylka et al , ; Zank et al , ; Verkhoglyadova et al , , ]. The latest multispacecraft observations of longitudinally distributed SEP fluxes indicate that neither shock characteristics (including the shock obliquity which changes throughout the SEP event) nor flare preconditioning alone can explain the observed properties of SEP events [ Cohen et al , ].…”
Section: Introductionmentioning
confidence: 99%